HPLC Method for the Determination of Lycopene in Crude Oleoresin Extracts - Sathish, Thadikamala; Udayakiran, Doradla; Himabindu, Kushala; Lakshmi Durga Sridevi, Patsamatla; Kezia, Devarapalli; Bhojaraju, Pullasi (Asian Journal of Chemistry, 2010)
A simple and sensitive isocratic RP-HPLC method with spectrophotometric detection (475 nm) was developed and validated for the determination of lycopene in crude plant extracts. The method utilizes Supelcosil LC-18 column (150 × 4.6 mm), 3 μm particle size and a mobile phase consisting of acetonitrile, methanol and tetrahydrofuran (70:25:5, % v/v) at a flow rate of 1.0 mL/min. The retention times of lycopene and astaxanthin (internal standard) were 14.2 and 3.0 min, respectively and the total run time was 15 min. Experiments were conducted at room temperature in the absence of direct sunlight. Calibration graph of standard lycopene was linear in the concentration range of 200-1000 ng/mL with the detection limit of 50 ng/mL. The method was validated for the concentration range 0.2-1.0 mg/mL. Intra-and inter-day relative standard deviations were less than 3.5